2015
DOI: 10.1038/srep15185
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acute non-visual bright light responses in patients with optic nerve disease, glaucoma and healthy controls

Abstract: This study examined the effect of optic nerve disease, hence retinal ganglion cell loss, on non-visual functions related to melanopsin signalling. Test subjects were patients with bilateral visual loss and optic atrophy from either hereditary optic neuropathy (n = 11) or glaucoma (n = 11). We measured melatonin suppression, subjective sleepiness and cognitive functions in response to bright light exposure in the evening. We also quantified the post-illumination pupil response to a blue light stimulus. All resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 59 publications
3
44
0
3
Order By: Relevance
“…Hence, ipRGCs consist of different subtypes and have several central targets. Both studies in mouse and human have shown that it is possible that one ipRGC end-point can be affected but not another (Chen et al 2011;Munch et al 2015). Furthermore, a recent study on rat retina reported that the M1 ipRGCs are more resistant to injury than other ganglion cells following optic nerve transection (Perez de Sevilla Muller et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, ipRGCs consist of different subtypes and have several central targets. Both studies in mouse and human have shown that it is possible that one ipRGC end-point can be affected but not another (Chen et al 2011;Munch et al 2015). Furthermore, a recent study on rat retina reported that the M1 ipRGCs are more resistant to injury than other ganglion cells following optic nerve transection (Perez de Sevilla Muller et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The density of ipRGCs is, however, reduced in both primary and secondary glaucoma. Correspondingly, the NIF effects of light, specifically the sustained pupillary response to short wavelength light and the light induced suppression of pineal melatonin, are most severely affected in advanced stages of glaucoma [15][16][17]. In our population, approximately 55% had visual field defects worse than 12 dB in the better eye indicating an advanced stage of disease.…”
Section: Plos Onementioning
confidence: 72%
“…These associations may be attributable to a disrupted central light input as well as to the psychological burden of a chronic progressive disease and the threat of blindness. Indeed, there is evidence of attenuated NIF-functions in glaucoma such as reduced pupillary responses to blue light [12][13][14][15][16], reduced light induced suppression of pineal melatonin release [17] and a reduced alerting response to light [16]. These dysfunctions can all be linked to the loss of retinal ganglion cells, specifically the ipRGCs.…”
Section: Introductionmentioning
confidence: 99%
“…Pupil responses to light in healthy persons [167][168][169][170] and patients with eye disease [171][172][173][174][175]…”
Section: (I) Physiological Differencesmentioning
confidence: 99%